Trois transitions, deux situations professionnelles, une vie : le cas des enseignants intermittents - Xavière Lanéelle (Nantes Université, 2011)
Intermittent teachers, substitute teachers, whether confirmed or not, who have acquired a different job or status live a triple transition: spatial, professional and towards the future. These transitions come along with mechanisms of adaptation which occur through strategies. Some are effective and allow the teacher a professional development which strengthens his identity in his job. It's the case for those which turn towards the improvement of professional skills by a strong commitment in the job or by continuing training. The integration in local social networks is also favorable. A realistic anticipation, the insertion in a fabric of local relationships, a compatible territorial anchoring are among the key factors to success. A contrario, one who hasn't benefited from these resources can nevertheless build himself up by leaning on a project which, if it comes to fulfilment, will improve his future. However some fail. The risk is then professional desocialization with all its threats.